(3eXGgQI GdeSYi GdLejd heMGPQI GdeQYi GdhHjds - (3CHhYHO Gddg eMeO Hf YHO Gddg Hf CHj HcQ GdbVGYj GdHdfSj Hf GdCHGQs; (3CHh GdYdGA GdeYQj , CHh GdYdGA CMeO Hf YHO Gddg Hf SdjeGf GdJfhMj GdeYQj,J (B449 (3g` s
(3ChdgG (B:s
(3MQa GdgeRI(B: (3Jbhi GdEdg fYe GdedLC, hGJHGY Gdghi HFS GdefHC s
(3BNQgG (B:s
(3hNjQ GdRGO Jbhi Gddg MbkG adG JYOd HJbhi Gddg TjG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3BNQgG KdGK hQbGJ CTYGQ ddeDda bGdgG aj HdfSjg hJhfSs
(3HChdgG hBNQgG SeGYGJ hbQGAGJ aj eYGQVI edbi GdSHjd dCHj GdYdGA GdeYQjs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B290s
Keywords: (3GdCOHs